ETHICAL CONSIDERATIONS FOR OUTCOME-ADAPTIVE TRIAL DESIGNS: A CLINICAL RESEARCHER'S PERSPECTIVE. - Saxman, Scott Brian (Bioethics, 2015)
In a typical comparative clinical trial the randomization scheme is fixed at the beginning of the study, and maintained throughout the course of the trial. A number of researchers have championed a randomized trial design referred to as 'outcome-adaptive randomization.' In this type of trial, the likelihood of a patient being enrolled to a particular arm of the study increases or decreases as preliminary information becomes available suggesting that treatment may be superior or inferior. While the design merits of outcome-adaptive trials have been debated, little attention has been paid to significant ethical concerns that arise in the conduct of such studies. These include loss of equipoise, lack of processes for adequate informed consent, and inequalities inherent in the research design which could lead to perceptions of injustice that may have negative implications for patients and the research enterprise. This article examines the ethical difficulties inherent in outcome-adaptive trials.